A Vajdaság útja az európai integrációba a Vajdaság AT Statútumának tükrében - Soós, Edit (Közép-Európai Közlemények, 2011)
This article sets out a conceptual basis for measuring Vojvodina’s regional autonomy in Serbia’s European perspective. Serbia is a potential candidate country for EU accession, implementation of the European Partnership (2008) will be examined through the mechanisms established under the stabilization and association process. In 2009, the Serbian Parliament ratified the new autonomy statute for Vojvodina. While the national government could not entirely close its eyes to the EU regionalization requirements the provincial government had the opportunity to express its demands. The Statute of Vojvodina was to set out the key principles that should underlie effective regional democracy, covering areas such as financial autonomy and legislative powers. Parallel with regional autonomy one sees the challenges of personal autonomy and Hungarian National Council in the sphere of freedoms relating to language, education and cross-border cooperation. The article concludes by examining measures of Hungary’s national policy towards capacities of AP Vojvodina, aiming at faster integration of Serbia, and Hungarian minority communities living in the border area.